ANALYSIS OF HEAVY METALS CONTENT Pb, Cr, Cu AND Zn IN SEA WATER AND SEDIMENT IN SINGKEP ISLAND LINGGA REGENCY OF KEPULAUAN RIAU PROVINCE - Azhari, Febbi; Siregar, Yusni Ikhwan; Amin, Bintal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in coastal waters of Singkep Island held on 28 Januari 2018 – 4 Februari 2018. The study aimed at analyzing Pb, Cr, Cu and Zn concentration in waters column as well as in sediment were taken from two stations with three replicates at each station.. Heavy metals were analyzed by following Hutagalung procedure (1991) and Yap et al., (2003). The results showed that the average content of heavy metals in Singkep water is 0.23 mg/l (Pb), 0.05 mg/l (Cr), 0.09 mg/l (Cu), and 0.43 mg/l (Zn), the sediment was 3.89 μg/g (Pb), μg/g, 18.53 (Cr), 2.08 μg/g (Cu), 38.67 μg/g (Zn). Simple linear regression analysis indicates negative correlation between Cr, Cu and Zn content in sea water and in sediment with Y =38.51 – 430.4x , r = 0.51 (Cr), Y =37.87 – 378.0x r = 0.88(Cu) ; and Y =45.74 – 16.31x, r = 0.11 ( Zn) and positive correlation between Pb content in sea water and in sediment with Y= -4.2241+ 34.19x, r = 0.71. The concentration of all metals measured in water exceeded the quality standard regulation. However, concentration of metals in sediments were below the ERL and ERM.Key Words : Singkep Island, Heavy Metal, Pollution, Seawater, Sediment